Application of the electric probe to the investigation of surface wave in piezoelectrics - FILIPIAK, Jerzy (Archives of Acoustics, 1989)
A system for vizualization of the surface acoustic wave in piezoelectrics is presented. The system for surface wave front amplitude and phase measurement in weak piezoelectrics have been described. The measuring capabilities of the system have been exemplified for the bismuth-germanium oxide and quartz type substrates.